Indonesia’s Effort to Improve Islamic Images in The United States During 2009-2017: A Case Study of Interfaith Dialogue - Hendra Maujana Saragih; Esca Hutama Prayogo Surya; Syifa Nur Islamiah (AJIS: Academic Journal of Islamic Studies, 2020)
Indonesia strives to improve the Islamic image in the United States during the year of 2009-2017. As an effort, Indonesia conducted interfaith dialogue as a diplomacy instrument with the United States known as the Indonesia-US Interfaith Dialogue. As regards the interfaith dialogue, the researchers then scrutinized the efforts of Indonesia to improve the Islamic image in the United States. The researchers used two concepts and one theory in this study, precisely the concept of national interests, the concept of foreign policy, and the concept of Public Diplomacy. This study applied a qualitative approach. The secondary data were taken from books, journals, theses, and official websites and news. The results of this study revealed that after conducting an Interfaith Dialogue with the United States during 2009-2017, the Islamic image in the United States raised to be positive. The positive’s improvement could be seen in US leaders who understood the true meaning of Islam in which Islam is a religion that brought peace as what was promoted by Indonesia